2017
DOI: 10.1111/febs.14350
|View full text |Cite
|
Sign up to set email alerts
|

Structure and interaction ofCorynebacterium pseudotuberculosiscold shock protein A with Y‐box single‐strandedDNAfragment

Abstract: Resonance assignment and structural data are available in the Biological Magnetic Resonance Data Bank and Protein Data Bank under accession number 26802 and 5O6F, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(213 reference statements)
0
3
0
Order By: Relevance
“…Overexpression of SP_2655 can significantly repress spinosyn αd production in the mutant S. pogona ‐Δ ura4‐ Δc14; however, the production of spinosyn αd increased significantly after SP_2655 was deletion in wild‐type strain, indicating that SP_2655 is a TetR family transcriptional factor that negatively regulates spinosyn αd biosynthesis. As another regulatory factor, cold shock protein A is an RNA chaperone that binds single‐stranded nucleic acids and destabilizes stem loop structures in nascent mRNA at low temperature, thus allowing transcription of downstream genes to continue under cold stress conditions (Wang et al ., 2014 ; Wang et al ., 2016 ; Caruso et al ., 2018 ). Whether deletion of SP_2649 can also cause related phenotypic changes in S. pogona needs to be further verified by genetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SP_2655 can significantly repress spinosyn αd production in the mutant S. pogona ‐Δ ura4‐ Δc14; however, the production of spinosyn αd increased significantly after SP_2655 was deletion in wild‐type strain, indicating that SP_2655 is a TetR family transcriptional factor that negatively regulates spinosyn αd biosynthesis. As another regulatory factor, cold shock protein A is an RNA chaperone that binds single‐stranded nucleic acids and destabilizes stem loop structures in nascent mRNA at low temperature, thus allowing transcription of downstream genes to continue under cold stress conditions (Wang et al ., 2014 ; Wang et al ., 2016 ; Caruso et al ., 2018 ). Whether deletion of SP_2649 can also cause related phenotypic changes in S. pogona needs to be further verified by genetic modification.…”
Section: Discussionmentioning
confidence: 99%
“…Short simulations of the Corynebacterium pseudotuberculosis cold shock protein A bound to an aptamer molecule were performed by Caruso [ 109 ]. They have shown that ssDNA can also rely on intermittent nonspecific hydrogen bond interactions, in addition to the salt-bridges, to confer complex stability [ 109 ]. Interactions between aromatic amino acids and the free nucleic acid bases contributed to an overall enthalpy energy gain.…”
Section: Molecular Dynamics Simulations Applied To Nucleic Acids (mentioning
confidence: 99%
“…CspA family proteins are small RNA binding proteins that are involved in bacterial response to environmental changes ( 30 32 ). P. aeruginosa harbors five CspA family proteins, namely, CspC (PA0456), PA0961, PA1159, CspD (PA2622), and CapB (PA3266) ( 33 ).…”
Section: Introductionmentioning
confidence: 99%